The Influence Of Hospitality And Service Quality Toward Tourist Satisfaction And Loyalty - Moh'd Bani-Khaled, Jehad Hasan (2020)
The purpose of this study is to provide an understanding of the influence of hospitality and service quality toward tourist satisfaction and loyalty.. This study also uses a causative model in solving some aspects of customer satisfaction and loyalty. The gap in this study forms the basis of the study, which is the means of the quality of services affecting the hotel services. More specifically, customer satisfaction and its impact on tourist loyalty is a key objective in promoting customers in Jordan. In this context, the relationship between tourist loyalty and its antecedents becomes the focus of the entire study. In this study, Structural Equation Modeling (SEM) was used by analyzing data in Partial Least Square (PLS) to understand the study questions and to get the most appropriate results by combining direct, latent, and factorial factors.